2009
DOI: 10.1074/jbc.m801324200
|View full text |Cite
|
Sign up to set email alerts
|

αII-Spectrin Is Critical for Cell Adhesion and Cell Cycle

Abstract: Spectrins are ubiquitous scaffolding components of the membrane skeleton that organize and stabilize microdomains on both the plasma membrane and the intracellular organelles. By way of their numerous interactions with diverse protein families, they are implicated in various cellular functions. Using small interfering RNA strategy in the WM-266 cell line derived from human melanoma, we found that ␣II-spectrin deficiency is associated with a defect in cell proliferation, which is related to a cell cycle arrest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 43 publications
2
88
0
1
Order By: Relevance
“…These include a role in the formation and maintenance of specialized plasma membrane domains defining apicalbasolateral and planar polarity in epithelial cells, muscle and neurons (Bennett and Baines, 2001); in the structural support of the plasma membrane and the maintenance of cell shape (Gallagher and Jarolim, 2000;Kizhatil et al, 2007); as a scaffold upon which calcium-mediated and tyrosine kinase-phosphatase signal transduction pathways converge (Nicolas et al, 2002;Nedrelow et al, 2003); as a tumor-suppressor protein involved in TGF-b-SMAD regulation (Tang et al, 2003); as a cargo selection mechanism in the secretory and endocytic pathways (De Matteis and Morrow, 2000); as a regulator of macropinocytosis (Xu et al, 2000); as a tether linking trafficking vesicles to microtubule motors (Holleran et al, 2001;Muresan et al, 2001); as a nuclear scaffold organizer (McMahon et al, 1999;Tse et al, 2001); and most recently, as a potential mechano-sensing ligand-binding switch (Stabach et al, 2009). Deletion of aII-spectrin in Drosophila melanogaster and Caenorhabditis elegans leads to late embryonic-early larval stage lethality (Moorthy et al, 2000;Dubreuil, 2006;Hammarlund et al, 2007), and recent knockdown studies of aII-spectrin in cultured cells have demonstrated growth and adhesion defects (Metral et al, 2009). However, the role of aII-spectrin in vertebrate development remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…These include a role in the formation and maintenance of specialized plasma membrane domains defining apicalbasolateral and planar polarity in epithelial cells, muscle and neurons (Bennett and Baines, 2001); in the structural support of the plasma membrane and the maintenance of cell shape (Gallagher and Jarolim, 2000;Kizhatil et al, 2007); as a scaffold upon which calcium-mediated and tyrosine kinase-phosphatase signal transduction pathways converge (Nicolas et al, 2002;Nedrelow et al, 2003); as a tumor-suppressor protein involved in TGF-b-SMAD regulation (Tang et al, 2003); as a cargo selection mechanism in the secretory and endocytic pathways (De Matteis and Morrow, 2000); as a regulator of macropinocytosis (Xu et al, 2000); as a tether linking trafficking vesicles to microtubule motors (Holleran et al, 2001;Muresan et al, 2001); as a nuclear scaffold organizer (McMahon et al, 1999;Tse et al, 2001); and most recently, as a potential mechano-sensing ligand-binding switch (Stabach et al, 2009). Deletion of aII-spectrin in Drosophila melanogaster and Caenorhabditis elegans leads to late embryonic-early larval stage lethality (Moorthy et al, 2000;Dubreuil, 2006;Hammarlund et al, 2007), and recent knockdown studies of aII-spectrin in cultured cells have demonstrated growth and adhesion defects (Metral et al, 2009). However, the role of aII-spectrin in vertebrate development remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, ICAM-4 molecules on SAD RBC could be gathered as clusters, enabling stronger binding to aVβ3 integrin clusters on endothelial cells. 31,32 Likewise, an increased clustering of CD36 on SAD RBC, as observed by electronic microscopy in platelet membranes, 33 may strengthen the interaction between erythrocyte CD36 and endothelial thrombospondin.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have demonstrated that the interaction of Lu/BCAM with erythroid spectrin negatively regulated its adhesive receptor function in normal and spectrin-deficient HS RBCs [15,18]. In non-erythroid adherent cells, partial DII-spectrin depletion was associated with loss of cell spreading, defective adhesion and decrease and irregularity of focal adhesion points [32].…”
Section: Discussionmentioning
confidence: 99%
“…The role of DII-spectrin in actin organization has been recently demonstrated, as DII-spectrin knocked-down melanoma WM-266 cells exhibited modifications of the actin cytoskeleton such as a loss of stress fibers [32]. DII-Spectrin, via its SH3 domain, has been also implicated in initiating Rac activation in the specialized E3 integrin clusters that initiate cell adhesion and spreading [35].…”
Section: Consequences On Actin Dynamicsmentioning
confidence: 99%